Results of an estimation of an integrated component of health of students. - Loshytska T.I (Kharkov National Pedagogical University, 2010)
Parities between muscular activity and reaction of heart are construed at dosed loading. Performances of different aspects of tests for determining a level of health of students are reduced. 3 groups of students took part in research on 17 person in everyone. It is emphasized, that the level of health can be described by two components: in power and not power (integration) potential. Directions of determining of a level of health of students are specified. It is exhibited parities between intensity (capacity) of an exercise stress and features of corresponding reaction on parameters of frequency of cardiac reductions.